IMPLEMENTATION OF GAGNE'S THEORY IN LEARNING FOR CHILDREN WITH ADHD - Bhanasya shafa Aurelia; Aziziah Oktaviana Sari (Journal of Disability, 2024)
This article explores the importance of implementing Gagne’s Theory in learning for children with Attention Deficit Hyperactivity Disorder (ADHD). Children with ADHD often struggle with maintaining focus, processing information efficiently, and retaining knowledge, making it crucial to adopt structured and adaptive learning approaches to support their educational needs. Gagne’s Theory, known for its systematic and sequential instructional principles, provides an effective framework for enhancing the learning experience of children with ADHD. This article outlines key principles of Gagne’s Theory and examines how they can be practically applied in learning environments to accommodate the unique challenges faced by children with ADHD. By implementing clear learning objectives, structured instruction, engaging stimuli, and reinforcement strategies, educators can create a more inclusive and supportive learning experience that helps ADHD students maximize their potential. The application of Gagne’s principles not only enhances academic achievement but also supports the development of self-regulation and cognitive skills, enabling children with ADHD to overcome learning barriers and thrive in educational settings.